WAVE ENERGY CONVERTER OUTPUT SPECIFICATIONS ON CONDITION OF WAVE AMPLITUDE INCREASE - Каріtanchuk Constantine; Andriyishyn Мykhailo (Science-based technologies, 2022)
Estimated power density of world’s marine energy is about 10-90 terawatts-hour and partially can be used by mankind. Ocean covers 75% of Earth surface and accumulates amounts of solar energy that is stored as wave energy, tide energy, current energy, osmotic energy and thermal energy. Current level of mankind technological advancement allows transforming these kinds of energy into electricity taping into this enormous course of transformed solar energy. With combined effort from members of National Aviation University, Admiral Makarov National University of Shipbuilding and Institute of Hydromechanics of NAS Ukraine a breakthrough version of wave energy converter was successfully designed, created and tested in a field. Designing a wave energy converter that will be durable, efficient and easy to installhas been the ultimate goal of research teams across the globe for a while. This method of calculating power output of wave energy converter power station allows to make changes into power station configuration based on changes in working conditions. According to coastline geometry, seasonal weather changes and actual demand for electrical power we can calculate dimensions of our station like length, radius of power take-off element etc. Math shows that width of power take-off element does not affect the rotation speed of a turbine. In case of increase of wave amplitude, compared to value used in theoretical calculation of specific station, the rotation speed of a turbine will drastically decrease. Article presents calculations of changes in wave energy converter station power output that occurs on condition of increase of wave amplitude for wave length of 9m and R/b = 2.